A deliberative public sphere? Picturing Portuguese political blogs - Silva,Elsa Costa e (2014)
Deliberative democracies are based on the principle of citizens participation. However, election turnouts and citizens alienation are signs of a political disengagement that could endanger the foundations of democratic systems. The spaces in which political debate and rational argumentation between equals may take place have diminished, yet new digital technologies have brought up potentialities in the promotion of online, horizontal and deliberative communication. Political blogs have been one of the most studied platforms, as they allow citizens engaged in political discussion and argumentation to establish a public sphere in which matters of public concern are debated. Nonetheless, issues of political polarization, fragmentation and non-rational debate have also been pointed out to limit the most optimistic perspectives over political blogs. By using the social network analysis, this paper aims to contribute to a better understanding of the role of Portuguese political blogs, by assessing its level of deliberation.